Reconstruction of the bottom current strength of overflow water through the Faeroe-Shetland Channel in relation to climate change during the last 135,000 years - Solheim, Martin (UiT Norges arktiske universitet, 2018)
The focus of this thesis was to reconstruct the bottom current strength around the Faeroe Islands and relate it to the climate variability over the past 35,000 - 135,000 years and the Holocene, using the piston core, JM11-FI-19PC, from the North-eastern shelf of the Faeroe Islands. The core location is ideal for measuring the overflow from the Nordic Seas, as it is strategically placed on top of the Greenland-Scotland Ridge. The investigated time interval includes the last glacial cycle, Weichselian, as well as the Holocene and Eemian. The results are based on sortable silt analysis, IRD and tephra counts, as well as material from previous studies of the investigated core. The results from this thesis is linking higher bottom current strength with interstadials throughout the Weichselian ice age, but also demonstrating that the circulation around the Faeroe Islands never ceased, but reversed. Material from other sources have provided evidence for a warm, subsurface current entering the Nordic Seas during stadials, and the results from this thesis demonstrate that there was a weaker current flowing over the investigated core during stadials. The bottom current strength measured in the results show clear relations to the climatic variabilities throughout the last glacial cycle, and also strongly suggest vertical shifts of currents and water masses, that are likely to be connected to the relative sea level.